2002
DOI: 10.1046/j.1365-3083.2002.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bcl‐2 and Reduced Bax Expression in Infected Macrophages in Slowly Progressive Primary Murine Mycobacterium tuberculosis Infection

Abstract: Mycobacterium tuberculosis (MTB) persists in host macrophages (Mfs) because it has developed mechanisms to escape Mf killing. In vitro studies have shown that MTB can induce and inhibit apoptosis by causing the expression of Bax and Bcl-2, respectively, suggesting that the infected cells' fate depends on pro-and antiapoptotic signals. In the present study, we investigated the role of Bcl-2 in MTB infection in situ. The aim was to study the pattern and distribution of Bcl-2 and Bax in cellular infiltrates of MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 44 publications
3
47
1
2
Order By: Relevance
“…This hypothesis is compatible with the in vitro data already published showing inhibition of apoptosis in infected macrophages by virulent M. tuberculosis (but not avirulent mycobacteria) [27,28,55,[59][60][61][62][63]. It is also consistent with multiple reports suggesting that upregulation of Fas/FasL in vivo is specifically associated with T-cell death in TB [38,[64][65][66][67].…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis is compatible with the in vitro data already published showing inhibition of apoptosis in infected macrophages by virulent M. tuberculosis (but not avirulent mycobacteria) [27,28,55,[59][60][61][62][63]. It is also consistent with multiple reports suggesting that upregulation of Fas/FasL in vivo is specifically associated with T-cell death in TB [38,[64][65][66][67].…”
Section: Discussionsupporting
confidence: 91%
“…The incomplete blocking of apoptosis in TNF-␣-cycloheximide-stimulated cells may have been due to inhibition of protein translation of transfected Bcl2 by cycloheximide. Interestingly, mycobacteria persisting in human macrophages upregulate Bcl2 to prolong survival of their host cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that antiapoptotic Bcl2 proteins play an impor- (33). Proapoptotic Bax has been found to be cleaved by calpain and to integrate in mitochondrial membranes to initiate programmed cell death (3), whereas proapoptotic Bid could be cleaved by caspase 8 and inhibit Bcl2 function (12).…”
Section: S Pneumoniae Induces Apoptosis In Human Alveolar Epithelialmentioning
confidence: 99%
“…It has been demonstrated that apoptosis, but not necrosis, is associated with killing of intracellular mycobacteria [2]. Thus, it has been hypothesized that inhibiting apoptosis of macrophages might be a survival strategy for virulent mycobacteria [3][4][5][6]. In vitro studies have shown that virulent mycobacterial strains induce less apoptosis of macrophages than non-virulent strains [7,8], but this has not been demonstrated in vivo in humans; which mycobacterial components are involved in the inhibition of apoptosis are not known either.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown earlier in murine lung lesions that M. tuberculosis strain H37Rv can influence the expression of apoptosis regulatory proteins by causing increased expression of FasL and Bcl-2 on the infected macrophages. This allows mycobacteria to inhibit apoptosis of the infected cells through increased expression of Bcl-2, and these cells will then escape activation and killing by Fas-expressing lymphocytes by their increased expression of FasL [4][5][6].…”
Section: Introductionmentioning
confidence: 99%